(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In recent years, several nations have made steps to combat workplace harassment anddomestic violence, but less attention has been devoted to sexual harassment in public areas, particularlyduring women’s commutes to work and school. Many more women are pursuing education and work indeveloping nations than in the past, which has raised the risk of sexual harassment in public settings. Thiskind of abuse is known as eve teasing in India, where the research was conducted. Catcalling, vulgarcomments, and unwanted sexual touch such as stroking and fondling are all examples of Eve teasing.Tolerance of such instances may escalate to more serious kinds of abuse and inspire more people totake part. Laws, as necessary as they are, cannot bring about instant changes in broad public practices,especially those that are strongly established in a country’s culture, such as eve teasing. In this study wehave discussed about the violence against Women to upset their Dignity, Eve Teasing and itsAggravated Form, Insulting Modesty of a Women, Vishaka Guidelines, Interpretation of Section 354 and509 of Indian Penal Code, Provoking a Woman’s Sense of Dignity, The Phrase Eve-Teasing, SexualHarassment and its Punishment, Voyeurism, Stalking, Eve-Teasing.